Using more than 801 296 small‐molecule crystal structures to aid in protein structure refinement and analysis. Addendum. Issue 12 (4th December 2017) - Cole, Jason C.; Giangreco, Ilenia; Groom, Colin R.
Abstract : An addendum to the article byCole et al. [(2017), Acta Cryst. D73, 234–239] . Abstract : An addendum to the Introduction of Cole et al. [(2017), Acta Cryst. D73, 234–239] is made to recognize the work of Bricogne, Smart and others in the development of methods to make use of Cambridge Structural Database data in protein structure solution.